2023
DOI: 10.1099/jmm.0.001657
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of genome-wide imipenem resistance features in Klebsiella pneumoniae using machine learning

Abstract: Introduction. The resistance rate of Klebsiella pneumoniae ( K. pneumoniae ) to imipenem is increasing year by year, and the imipenem resistance mechanism of K. pneumoniae is complex. Therefore, it is urgent to develop new strategies to explore the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Reduction in the cost and time required for WGS has enabled researchers to develop WGS-based antimicrobial susceptibility/resistance testing using machine-learning computational methods [ 86 , 87 ]. Machine-learning methods can effectively predict the imipenem resistance feature in K. pneumoniae and provide resistance sequence profiles for predicting resistance phenotypes and exploring potential resistance mechanisms [ 88 ]. By combining WGS of 1,113 pre- and post-treatment bacterial isolates with machine-learning analysis of 140,349 urinary tract infections and 7,365 wound infections, Stracy et al [ 89 ] reported that treatment-induced emergence of AMR could be predicted and minimized at the individual-patient level.…”
Section: Identification Of Amr Genes/determinants By Wgsmentioning
confidence: 99%
“…Reduction in the cost and time required for WGS has enabled researchers to develop WGS-based antimicrobial susceptibility/resistance testing using machine-learning computational methods [ 86 , 87 ]. Machine-learning methods can effectively predict the imipenem resistance feature in K. pneumoniae and provide resistance sequence profiles for predicting resistance phenotypes and exploring potential resistance mechanisms [ 88 ]. By combining WGS of 1,113 pre- and post-treatment bacterial isolates with machine-learning analysis of 140,349 urinary tract infections and 7,365 wound infections, Stracy et al [ 89 ] reported that treatment-induced emergence of AMR could be predicted and minimized at the individual-patient level.…”
Section: Identification Of Amr Genes/determinants By Wgsmentioning
confidence: 99%